The Role of Superplasticizers on the Workability Consistency of ECC Mortar Fresh Mortar Due to an Increase in the Percentage of Palm Shell Ash - Agussalim Lubis; Muhammad Aswin; Gina Cynthia Raphita Hasibuan (CV. Publikasi Indonesia, 2024)
Engineered cementitious composites (ECCs) are composites that have better attraction properties and behavior than concrete. ECCs are usually formed from cement, water, silica sand, cementitious materials, fibers, and other additives with a certain proportion. In this study, there are three types of ECC mortars (types AME, EM, and TEM) where these types are differentiated by the amount of cement used, the quantity of water, and the number of sand used. Each type uses ashes of palm shells with the same proportions of 0%, 5%, 10%, and 15% of the weight of cement. According to trial and error during the workability test, the number of superplasticizers used also increased according to the increase in the percentage of ash in the palm shell, where the variation of superplasticizers achieved was 0.70%, 1.59%, 2.49%, and 3.40% of the weight of cement. Based on the results of the slumpflow test, the average diameter of the ECC freshly mixed mortar was between 88 cm and 106.5 cm, and the T500 slump flow was between 0.28 seconds and 1.39 seconds. The test results show a fairly good workability consistency of all ECC fresh mortars, although there has been an increase in the percentage of palm shell ash used. Superplasticizer turns out to be very important in maintaining consistent workability of fresh ECC mortar mix.